An HPC-based Prediction on the Practicality of Long-distance Quantum Key Distributions - Ryu, Hoon; Kang, Ji-Hoon (Proceedings / IEEE International Conference on Cluster Computing, 2020)
Practicality of long-distance quantum communications based on a BB84 quantum key distribution (QKD) protocol is examined with Monte Carlo simulations coupled to a parallel computing. Given a quantum channel that is not free from noises, optimal sizes of the shared key information and corresponding chances for detecting the eavesdropper are calculated to present clues that can be utilized to figure out the utility of the protocol. Delivering simple but sound principles that have not been focused quite well, this work serves as a useful case study that shows the need of high performance computing for QKD modeling, and can trigger potential efforts for further modeling studies that involve more realistic and complicated factors.